Contribution of airway eosinophils in airway wall remodeling in asthma: Role of MMP‐10 and MET. Issue 6 (11th February 2019) - Kuo, Chih‐Hsi S.; Pavlidis, Stelios; Zhu, Jie; Loza, Matthew; Baribaud, Fred; Rowe, Anthony; Pandis, Ioannis; Gibeon, David; Hoda, Uruj; Sousa, Ana; Wilson, Susan J.; Howarth, Peter; et al.
Abstract: Background: Eosinophils play an important role in the pathophysiology of asthma being implicated in airway epithelial damage and airway wall remodeling. We determined the genes associated with airway remodeling and eosinophilic inflammation in patients with asthma. Methods: We analyzed the transcriptomic data from bronchial biopsies of 81 patients with moderate‐to‐severe asthma of the U‐BIOPRED cohort. Expression profiling was performed using Affymetrix arrays on total RNA. Transcription binding site analysis used the PRIMA algorithm. Localization of proteins was by immunohistochemistry. Results: Using stringent false discovery rate analysis, MMP‐10 and MET were significantly overexpressed in biopsies with high mucosal eosinophils (HE) compared to low mucosal eosinophil (LE) numbers. Immunohistochemical analysis confirmed increased expression of MMP‐10 and MET in bronchial epithelial cells and in subepithelial inflammatory and resident cells in asthmatic biopsies. Using less‐stringent conditions (raw P ‐value < 0.05, log2 fold change > 0.5), we defined a 73‐gene set characteristic of the HE compared to the LE group. Thirty‐three of 73 genes drove the pathway annotation that included extracellular matrix (ECM) organization, mast cell activation, CC‐chemokine receptor binding, circulating immunoglobulin complex, serine protease inhibitors, and microtubule bundle formation pathways. Genes including MET and MMP10 involved in ECM organization correlated positively with submucosal thickness. Transcription factor binding site analysis identified two transcription factors, ETS‐1 and SOX family proteins, that showed positive correlation with MMP10 and MET expression. Conclusion: Pathways of airway remodeling and cellular inflammation are associated with submucosal eosinophilia. MET and MMP‐10 likely play an important role in these processes. Abstract : Analysis of differentially expressed genes in eosinophil‐high biopsies of asthma yielded MMP10 and MET as potential drivers of airway wall remodeling. Important pathways include extracellular matrix organization, mast cell activation, C‐C receptor binding, and regulation of leukocyte activation. Bronchial eosinophils are important drivers of airway wall remodeling in asthma. MMP10: Matrix metalloprotease 10 gene. MET: Hepatocyte growth factor receptor gene.